EPIDEMIOLOGY AND MANAGEMENT OF GOUT PATIENTS ATTENDING RHEUMATOLOGY TERTIARY CENTRE IN PERAK, MALAYSIA. - Wahinuddin Sulaiman; Nurul Wahida Md Zuki; Norshamiza Zamri; Sandheep Suganthan; Aris Chandran Abdullah; Ong Ping Seung (Asian Journal of Medicine & Health Sciences, 2019)
Introduction: Gout is the most common treatable inflammatory arthritis worldwide. There is yet any prevalence study on gout on Malaysian population. The management of gout appears to be affected mostly by multiethnic perceptions, knowledge and awareness as well as variation in the treatment by different health care professionals and limitations in treatment modalities. The aim of this study is to describe the epidemiology and management of gout in rheumatology center in Perak state, Malaysia. Methods: All patients who were diagnosed as having gouty arthritis based on the 2015 American College of Rheumatology (ACR) classification criteria for gout and who had attended the rheumatology clinic, Hospital Raja Permaisuri Bainun, Perak, Malaysia were selected. Patient’s information was retrieved from the clinical records. Results: Fifty-four gout patients who were studied were predominantly from the Malay ethnic group followed by Chinese and Indian. The mean age was 53 years and the duration of disease was more than 10 years with male predominance. Forty-two patients had comorbidities which were hypertension, dyslipidemia, diabetes mellitus and ischemic heart disease. The most common manifestation was multiple joint pain, first metatarsophalangeal joint being most affected. Majority of the patients presented with tophi as well as other symptoms and signs of gout. The mean baseline serum uric acid (sUA) was 567.3 umol/L and 469.3 umol/L was six months after the treatment. The mean difference shown between sUA for males and females was statistically significant (P = 0.012) although the male patients were outnumbered. Majority of the patients were on urate-lowering therapy (ULT) namely allopurinol and probenecid. However, despite being advised, educated and given counselling sessions on allopurinol and diet, only half of them had shown good compliance. Conclusion: The targeted sUA as recommended in the guideline had yet to be achieved in our rheumatology clinic. The identification of reversible risk factors such as non-adherence to treatment, limited availability and accessibility of newer ULT, and dietary compliance in this study will provide guidance for better clinical management of gout in this region.